High-temperature-resistant sealing filling material and preparation method thereof

A high-temperature resistant sealing and filling material was prepared by combining composite metal oxide powder with sodium silicate and sodium fluorosilicate, which solved the sealing and heat protection problems of spacecraft in high-temperature environments and achieved effective sealing and bonding at 1200℃.

CN120987626APending Publication Date: 2025-11-21XIAN SPACE ENGINE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510945329.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing spacecraft sealing materials are difficult to effectively seal and protect against heat in high-temperature environments, especially in the annular metal gaps of the engine. Existing materials are not heat-resistant enough to meet the high-temperature requirements of 500-800℃.

Method used

The composite material uses high-temperature resistant fillers and binders, including high-alumina fine powder, chromium trioxide, boron trioxide, magnesium oxide, silicon dioxide, titanium dioxide, calcium oxide, zirconium oxide and other metal oxide powders, combined with sodium silicate and sodium fluorosilicate as binders and curing agents, and forms a high-temperature resistant sealing and filling material through mixing and curing.

Benefits of technology

The prepared material maintains good performance at a high temperature of 1200℃, and has excellent heat resistance, sealing performance and bonding strength. It has a low thermal weight loss rate and is suitable for the high temperature environment of spacecraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120987626A_ABST
    Figure CN120987626A_ABST
Patent Text Reader

Abstract

The invention provides a high-temperature-resistant sealing filling material and a preparation method thereof. The preparation method comprises the following steps: respectively weighing the high-aluminum fine powder, the chromic oxide, the diboron trioxide, the magnesium oxide, the silicon dioxide, the titanium dioxide, the calcium oxide and the zirconium oxide powder in proportion, and uniformly mixing and stirring to obtain the component A high-temperature-resistant powder; weighing sodium fluosilicate, grinding and sieving to obtain a component B; weighing a sodium silicate solution, and hydrolyzing to obtain a component C; the component A, the component B and the component C are mixed according to a certain mass ratio and are rapidly and uniformly stirred to obtain the high-temperature-resistant sealing filling material. The prepared high-temperature-resistant sealing and filling material can be used for filling and sealing of metal and ceramic materials and can resist the high temperature of 1200 DEG C, the thermal weight loss ratio at the temperature of 1200 DEG C is smaller than 0.035%, and the normal-temperature shear strength (aluminum-aluminum) can reach 4.6 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of aerospace materials, and particularly relates to a high-temperature-resistant sealing and filling material and a preparation method thereof. BACKGROUND

[0002] With the continuous development of aerospace technology, a large amount of research work has been carried out on special adhesives and sealing technology in the field of aerospace materials. The sealing and filling materials used in spacecraft such as carrier rockets, satellites and spaceships have higher performance requirements than the materials used in general industrial fields. At present, the adhesives used are mostly organic adhesives, such as acrylate urethane and silicone rubber, and the heat resistance of these adhesives can only reach about 250 DEG C. At present, most of the high-temperature-resistant materials are silicone materials. These high-temperature-resistant materials can meet the use requirements in high-temperature environments as protective materials for metal parts, but they are rarely used as high-temperature-resistant sealants for metal gaps. In the field of aerospace applications, local heat protection and sealing and bonding problems need to be solved in some parts of the engine, such as annular metal gaps, and high-temperature-resistant sealing materials capable of resisting temperatures of 500-800 DEG C are required. Therefore, the research on high-temperature-resistant sealing and filling materials is imminent. SUMMARY

[0003] The present application provides a high-temperature-resistant sealing and filling material and a preparation method thereof, which solves the problems of local heat protection and sealing and bonding in some parts of a spacecraft.

[0004] In a first aspect, a high-temperature-resistant sealing and filling material is provided, which comprises a high-temperature-resistant filler, an adhesive and a curing agent, wherein the high-temperature-resistant filler is a metal oxide powder comprising high-aluminum fine powder, chromium sesquioxide, boron sesquioxide, magnesium oxide, silicon dioxide, titanium dioxide, calcium oxide and zirconium oxide, the adhesive comprises sodium silicate, and the curing agent comprises sodium fluorosilicate.

[0005] In combination with the first aspect, in some implementations of the first aspect, the high-temperature-resistant filler, the curing agent and the adhesive are prepared in the following proportions by weight: 70-90 parts of the high-temperature-resistant filler, 8-12 parts of the curing agent and 85-95 parts of the adhesive.

[0006] In combination with the first aspect, in some implementations of the first aspect, the mass fractions of the substances in the high-temperature-resistant filler satisfy: 48-55 parts of high-aluminum fine powder, 10-15 parts of chromium sesquioxide, 2.0-3.0 parts of boron sesquioxide, 0.1-0.4 parts of magnesium oxide, 8-15 parts of silicon dioxide, 1.5-3.5 parts of titanium dioxide, 0.5-1.0 parts of calcium oxide and 0.1-0.3 parts of zirconium oxide.

[0007] In combination with the first aspect, in some implementations of the first aspect, the high-aluminum fine powder has an aluminum content of ≥70%.

[0008] In combination with the first aspect, in some implementations of the first aspect, the sodium silicate satisfies at least one of the following:

[0009] The sodium silicate has a sodium oxide Na2O content of 8.5% and a silicon dioxide SiO2 content of 27.3%;

[0010] The sodium silicate has a modulus of 2.4 and a Ph value of 8-10.

[0011] In combination with the first aspect, in some implementations of the first aspect, the Na2SiF6 content of the curing agent is not less than 99.0%.

[0012] In combination with the first aspect, in some implementations of the first aspect, the particle size of the chromium sesquioxide, boron sesquioxide, magnesium oxide, silicon dioxide, titanium dioxide, calcium oxide, and zirconium oxide ranges from 0.1 to 10 μm.

[0013] The second aspect provides a preparation method of the high-temperature-resistant sealing and filling material as described in any one of the implementations of the first aspect, comprising:

[0014] The high-alumina fine powder, chromium sesquioxide, boron sesquioxide, magnesium oxide, silicon dioxide, titanium dioxide, calcium oxide, and zirconium oxide are weighed, ground, and sieved to obtain high-temperature-resistant filler mixed particles;

[0015] The sodium fluosilicate is placed in a mortar, ground, dispersed, and sieved to obtain curing agent particles;

[0016] The obtained curing agent particles are added to the obtained high-temperature-resistant filler mixed particles, stirred, ground, and sieved to obtain solid material mixture;

[0017] The sodium silicate solution is added to the obtained solid material mixture, and the mixture is stirred uniformly to obtain the high-temperature-resistant sealing and filling material.

[0018] In combination with the second aspect, in some implementations of the second aspect, the preparation method satisfies at least one of the following:

[0019] The high-alumina fine powder is obtained by grinding and sieving bauxite, and the sieving mesh number is 320 mesh;

[0020] The sieving mesh number of the solid material mixture is 270 mesh;

[0021] The mass ratio of the adhesive to the solid material mixture is (45-50):(50-55);

[0022] The curing condition of the high-temperature-resistant sealing and filling material is room temperature curing, and the curing time is 24 hours.

[0023] The third aspect provides an application of the high-temperature-resistant sealing and filling material, which is the high-temperature-resistant sealing and filling material as described in any one of the implementations of the first aspect to the second aspect.

[0024] Compared with the prior art, the scheme provided by the present application has at least the following beneficial technical effects:

[0025] The present application adopts a low-cost, low-energy-consumption, simple raw material mixing preparation method to prepare a high-temperature-resistant sealing and filling material. In the preparation process, high-temperature-resistant metal oxides are used as high-temperature-resistant fillers, which have certain high-temperature mechanical properties and good volume stability. In the high-temperature-resistant material, a sodium silicate solution is used as an adhesive, and after the evaporation of water, the sodium silicate solution can form a relatively thick inorganic film on the surface of the high-temperature component, which plays an effective heat insulation role, and a solidifying agent sodium fluorosilicate is added for strengthening. The high-temperature-resistant sealing and filling material can be used for filling the annular gap between the nozzle of the engine thrust chamber and the mounting sleeve of the cabin, preventing hot gas from invading during the ascent of the spacecraft, and achieving excellent high-temperature-resistant sealing and filling effect.

[0026] The present application uses metal oxides as high-temperature-resistant fillers to reduce the thermal expansion coefficient and solidification shrinkage, improve the adhesive strength, heat resistance and wear resistance, and at the same time increase the viscosity of the glue solution and improve the thixotropy. The sodium silicate aqueous solution is used as an adhesive component, and the composite filler system ensures that the material has good heat resistance and sealing performance, forming a high-temperature-resistant, high-energy silicon-oxygen bond macromolecule, which is further solidified to form a silica network skeleton structure. The sodium silicate aqueous solution is hydrolyzed to produce SiO2, and the surface of SiO2 adsorbs hydroxyl groups, which reacts with Na + forms electrostatic action, making the material system structure stable, the bonding strength high, the high-temperature strength small, and the heat resistance, water resistance and acid resistance good. The use of high-aluminum fine powder improves the compactness of the material, and the high-aluminum fine powder reacts with silicates to form silico-aluminates during the high-temperature process, making the adhesive film have excellent high-temperature resistance. The addition of zirconium oxide, magnesium oxide and calcium oxide to the system stabilizes the crystal type transformation, increases the melting point and improves the compactness. The use of chromium trioxide greatly reduces the viscosity of the adhesive, reduces the content of the adhesive and water, and also plays a role in preventing cracking. Finally, a high-temperature-resistant sealing and filling material with good high-temperature-resistant performance and high adhesive strength is designed and prepared.

[0027] Compared with traditional high-temperature-resistant materials, the high-temperature-resistant sealing and filling material prepared by the present application has the advantages of low cost, easy preparation, high-temperature resistance and strong adhesive performance. The high-temperature-resistant filler prepared by the present application has a small particle size, and the particle size distribution is more than 90% below 40 μm. The high-temperature-resistant sealing and filling material prepared by the present application can withstand a minimum temperature of 1200°C, and the thermal weight loss rate of the sample is 0.035%. When bonded to an aluminum alloy test plate, the shear strength can reach 4.6 MPa. BRIEF DESCRIPTION OF DRAWINGS

[0028] Figure 1 TEM photo of the high-temperature-resistant sealing and filling material prepared in Example 1 after curing.

[0029] Figure 2 The macro-morphology of the high-temperature resistant sealing and filling material prepared in Example 1 before and after high-temperature is shown in the figure. DETAILED DESCRIPTION

[0030] The application will be further described in detail below in combination with the drawings and specific examples.

[0031] The application provides a high-temperature resistant sealing and filling material, wherein the high-temperature resistant filler is metal oxide powder, the metal oxide powder comprises high-aluminum fine powder, chromium sesquioxide, boron sesquioxide, magnesium oxide, silicon dioxide, titanium dioxide, calcium oxide and zirconium oxide, the binder comprises sodium silicate, and the curing agent comprises sodium fluorosilicate.

[0032] Preferably, the high-temperature resistant filler, the curing agent and the binder in the component are prepared in the following weight parts: 70-90 parts of the high-temperature resistant filler, 8-12 parts of the curing agent and 85-95 parts of the binder.

[0033] Preferably, the mass parts of the high-aluminum fine powder, the chromium sesquioxide, the boron sesquioxide, the magnesium oxide, the silicon dioxide, the titanium dioxide, the calcium oxide and the zirconium oxide in the component satisfy: 48-55 parts of the high-aluminum fine powder, 10-15 parts of the chromium sesquioxide, 2.0-3.0 parts of the boron sesquioxide, 0.1-0.4 parts of the magnesium oxide, 8-15 parts of the silicon dioxide, 1.5-3.5 parts of the titanium dioxide, 0.5-1.0 parts of the calcium oxide and 0.1-0.3 parts of the zirconium oxide.

[0034] Preferably, the aluminum content of the high-aluminum fine powder is greater than or equal to 70%.

[0035] Preferably, the binder is liquid sodium silicate.

[0036] Preferably, the modulus of the liquid sodium silicate is 2.4, and the Ph value is 8-10.

[0037] Preferably, the sodium oxide (Na2O) content in the liquid sodium silicate is 8.5%, and the silicon dioxide (SiO2) content is 27.3%.

[0038] Preferably, the Na2SiF6 content in the curing agent is not less than 99.0%.

[0039] Preferably, the particle size range of the chromium sesquioxide, the boron sesquioxide, the magnesium oxide, the silicon dioxide, the titanium dioxide, the calcium oxide and the zirconium oxide is 0.1-10 μm.

[0040] The application further provides a preparation method of the high-temperature resistant sealing and filling material, which specifically comprises the following steps.

[0041] (1) The high-aluminum fine powder, the chromium sesquioxide, the boron sesquioxide, the magnesium oxide, the silicon dioxide, the titanium dioxide, the calcium oxide and the zirconium oxide are weighed and ground and sieved to obtain high-temperature resistant filler mixed particles;

[0042] (2) Put sodium fluosilicate into a mortar, grind and disperse, and sieve to obtain solidifier particles;

[0043] (3) Add the obtained solidifier particles to the obtained high-temperature-resistant filler mixed particles, stir, grind, sieve, and obtain solid material mixture;

[0044] (4) Add a sodium silicate solution to the obtained solid material mixture, stir uniformly, and obtain the high-temperature-resistant sealing and filling material.

[0045] The selected high-temperature-resistant filler in the present application is a composite filler system composed of multiple metal oxide powders, wherein high-aluminum fine powder takes Al2O3 as the main element. The molecular structure of Al2O3 is hexagonal closest packing type. Since the Al-O bond in the crystal lattice has extremely high bonding performance, the structural stability is high at high temperature, and phase change is not easy to occur. It has high hardness, high compressive strength, and high Young's modulus, good thermal shock stability, and extremely high resistance to strong hot oxidation corrosion under high temperature conditions, but the material toughness is poor, and the thermal expansion coefficient is large, so the thermal shock resistance is poor. Therefore, Cr2O3 and SiO2 are added to form an Al2O3-SiO2-Cr2O3 composite filler system. SiO2 can improve physical properties such as low dielectric constant, low thermal expansion, high melting point, high creep resistance, high temperature mechanical stability, and high thermal performance impact resistance and chemical corrosion resistance. Cr2O3 has good thermal expansion performance. Under high temperature, this structure can effectively withstand the stress caused by thermal expansion, and is not easy to cause lattice damage. In addition, Cr2O3 has high hardness, and can improve the wear resistance after being added.

[0046] The system of the present application itself is a porous structure system, so MgO is added to improve the thermal shock resistance, TiO2 is added to improve the density, hardness and fracture toughness, and reduce the porosity. ZrO2 has small volume change during high temperature phase change, which can reduce the strain of the material during the thermal process and improve the heat resistance. The trace components do not have too much influence on the heat resistance and hardness, and good organizational structure, wear resistance, wet resistance and thermal shock resistance can be obtained, so that the performance of the material is more excellent.

[0047] The selected high-temperature-resistant filler of the present application provides excellent flowability for the material system, improves the particle packing effect, and greatly improves the thermal mechanical properties of the sealing adhesive. The cohesive strength, adhesion, and heat resistance of the sealing adhesive are improved. The curing shrinkage rate and the thermal expansion coefficient of the sealing adhesive are reduced.

[0048] The present application selects sodium silicate as the adhesive. First, trace amounts of moisture and carbon dioxide in the air induce the hydrolysis reaction of sodium water glass, and the reaction equation is shown as formula (1)-(2).

[0049] Na2SiO3 + 2H2O → 2NaOH + H2SiO3↓ Formula (1)

[0050] Na2SiO3 + 2CO2 + H2O → 2NaCO3 + H2SiO3↓ Equation (2)

[0051] With the reaction going on, the silicic acid (H2SiO3) in the system gradually precipitates the newly formed SiO2 colloid with great activity, and its reaction equation is shown in Equation (3).

[0052] H2SiO3→SiO2(colloid) + H2O Equation (3)

[0053] The SiO2 colloid can diffuse along the surface of the adherend to the interior of the adhesive layer, following the diffusion-limited aggregation model and the diffusion-limited cluster aggregation model, and when it reaches the active point position on the surface of the adherend, it forms an adhesive bond with the adherend in the form of a chemical bond. Under the alkaline condition of the reaction to generate sodium hydroxide (NaOH), the solubility of SiO2 increases, and the active points on the surface of SiO2 activate the terminal hydroxyl groups with the hydrolysis reaction. The SiO2 colloid precipitated by dehydration will rapidly diffuse along the interface between the high-temperature-resistant sealing material and the metal substrate, and form a -Si-O- bond with the terminal hydroxyl groups on the interface.

[0054] The NaOH produced by the hydrolysis of sodium silicate reacts further with the curing agent sodium fluorosilicate (Na2SiF6), and the reaction mechanism is shown in Equation (4):

[0055] Na2SiF6 + 4NaOH → 6NaF + Si(OH)4 Equation (4)

[0056] The silicon gel (Si(OH)4) produced by the reaction undergoes a dehydration reaction, as shown in Equation (5):

[0057] ≡Si–OH + OH–Si≡ → ≡Si–O–Si≡ + H2O Equation (5)

[0058] With the continuous progress of the reaction, the Si elements in sodium silicate (Na2SiO3) and sodium fluorosilicate (Na2SiF6) in the system are all converted into the Si-O-Si three-dimensional network structure, making the high-temperature-resistant sealing and filling material harden and have very high cohesive strength, forming a bonded joint with certain bonding force that can withstand a certain load. In addition to the polar bond action mechanism produced by the chemical reaction, the high-temperature-resistant sealing and filling material also has a mechanical bonding force effect, that is, the unhardened high-temperature-resistant sealing and filling material is injected into the uneven part of the bonding interface, and after hardening, the high-temperature-resistant sealing and filling material and the substrate are staggered and inlaid, producing an interaction force.

[0059] The particle size of the high-temperature resistant filler selected in the application is fine, which can play a supplementing role in the process of forming inorganic network structure of sodium silicate (Na2SiO3) and sodium fluorosilicate (Na2SiF6) in the system. The surface activity of the refractory filler particles can be combined with several macromolecular chains to form a cross-linked structure. When one of the molecular chains is stressed, the stress can be dispersed and transmitted to other molecules through the cross-linking points. Local micro-cracks are generated to release stress, so the use performance of the entire material can be greatly improved.

[0060] The application uses metal oxides as high-temperature resistant fillers to reduce the thermal expansion coefficient and solidification shrinkage, improve the bonding strength, heat resistance and wear resistance, increase the viscosity of the glue solution and improve the thixotropy. The sodium silicate aqueous solution is used as the adhesive component, and the composite filler system ensures that the material has good heat resistance and sealing performance, forms a high-energy silicon-oxygen bond macromolecule with high heat resistance, and further solidifies to form a silica network skeleton structure. The sodium silicate aqueous solution hydrolyzes to generate SiO2, and the hydroxyl groups on the surface of SiO2 are adsorbed to form a stable structure with Na + The static electricity is formed to make the material system structure stable, the bonding strength high, the high-temperature strength small, the heat resistance, water resistance and acid resistance good. The high-aluminum fine powder is used to improve the density of the material, and the high-aluminum fine powder reacts with silicates to generate silico-aluminates with excellent high-temperature resistance in the high-temperature process. Zirconium oxide, magnesium oxide and calcium oxide are added to the system to stabilize the crystal transformation, improve the melting point and the density, thereby enhancing the structure tightness and durability of the material and greatly improving the sealing performance after heat resistance.

[0061] Preferably, the high-aluminum fine powder is ground and sieved from bauxite, and the sieving mesh number is 320 meshes.

[0062] Preferably, the high-temperature resistant filler and the curing agent sodium fluorosilicate are sequentially added, uniformly mixed, and then oscillation ground and sieved, and the sieving mesh number is 270 meshes to obtain a solid material mixture.

[0063] Preferably, the adhesive liquid sodium silicate is added to the solid material mixture, the mass ratio of the adhesive to the solid material mixture is 45-50:50-55, and the liquid sodium silicate is uniformly mixed and stirred with the solid material mixture.

[0064] Preferably, the glass rod is used for rapid stirring after uniform mixing and stirring, and a high-temperature resistant sealing and filling material is obtained.

[0065] Preferably, the curing conditions of the high-temperature resistant sealing and filling material are room temperature curing (for example, the temperature is (23±5)℃), and the curing time is 24h.

[0066] The application further provides the application of the high-temperature-resistant sealing and filling material. The high-temperature-resistant sealing and filling material prepared according to the application is an inorganic adhesive with low cost, low energy consumption, high-temperature resistance of 1200 DEG C and strong sealing property. Preferably, the high-temperature-resistant sealing and filling material can be added to materials such as coating materials, fibers, ceramics, glass, metals and the like. More preferably, the high-temperature-resistant sealing and filling material can be added to the fields of mechanical manufacturing, automobiles, electronics, ships, aerospace and construction, and used for bonding, fixing, holding, sealing, encapsulation, coating and the like.

[0067] Example 1

[0068] A preparation method of a high-temperature-resistant sealing and filling material, comprising the following steps:

[0069] 2.5g of boric anhydride, 0.2g of magnesium oxide, 48g of high-aluminum powder, 10g of silicon dioxide, 0.6g of calcium oxide, 2g of titanium dioxide, 15g of chromium sesquioxide and 0.1g of zirconium oxide are weighed respectively, mixed and stirred to obtain mixed refractory powder. After 10g of sodium fluorosilicate is ground and sieved, it is added to the mixed refractory powder, and after mixing and stirring, it is oscillated, ground and sieved through a 270-mesh sieve to obtain solid material mixture. The solid material mixture is weighed and used as needed; 88g of sodium silicate solution is weighed according to the proportion, and a high-temperature-resistant sealing and filling material is obtained. After mixing and uniform stirring, the high-temperature-resistant sealing and filling material has high-temperature resistance after being solidified at room temperature for 24 hours.

[0070] Example 2

[0071] A preparation method of a high-temperature-resistant sealing and filling material, comprising the following steps:

[0072] 3.0g of boric anhydride, 0.3g of magnesium oxide, 52g of high-aluminum powder, 10g of silicon dioxide, 0.6g of calcium oxide, 2g of titanium dioxide, 13g of chromium sesquioxide and 0.1g of zirconium oxide are weighed respectively, mixed and stirred to obtain mixed refractory powder. After 8g of sodium fluorosilicate is ground and sieved, it is added to the mixed refractory powder, and after mixing and stirring, it is oscillated, ground and sieved through a 270-mesh sieve to obtain solid material mixture. 85g of sodium silicate solution is weighed according to the proportion, and a high-temperature-resistant sealing and filling material is obtained. After mixing and uniform stirring, the high-temperature-resistant sealing and filling material has high-temperature resistance after being solidified at room temperature for 24 hours.

[0073] Example 3

[0074] A preparation method of a high-temperature-resistant sealing and filling material, comprising the following steps:

[0075] Take 2.0g boron trioxide, 0.1g magnesium oxide, 50g high-alumina powder, 8g silicon dioxide, 0.5g calcium oxide, 1.5g titanium dioxide, 14g chromium trioxide and 0.1g zirconium oxide respectively, mix and stir to obtain mixed refractory powder. After grinding and sieving, 10g sodium fluorosilicate is added to the mixed refractory powder, mixed and stirred, then oscillation ground and sieved through a 270 mesh sieve to obtain a solid material mixture. Take 85g sodium silicate solution to obtain a high-temperature-resistant sealing and filling material. After mixing and stirring, the mixture is uniformly solidified at room temperature for 24 hours to obtain a high-temperature-resistant sealing and filling material.

[0076] Example 4

[0077] A method for preparing a high-temperature-resistant sealing and filling material, comprising the following steps:

[0078] Take 2.0g boron trioxide, 0.1g magnesium oxide, 50g high-alumina powder, 8g silicon dioxide, 0.5g calcium oxide, 1.5g titanium dioxide, 14g chromium trioxide and 0.1g zirconium oxide respectively, mix and stir to obtain mixed refractory powder. After grinding and sieving, 10g sodium fluorosilicate is added to the mixed refractory powder, mixed and stirred, then oscillation ground and sieved through a 270 mesh sieve to obtain a solid material mixture. Take 85g sodium silicate solution to obtain a high-temperature-resistant sealing and filling material. After mixing and stirring, the mixture is uniformly solidified at room temperature for 24 hours to obtain a high-temperature-resistant sealing and filling material.

[0079] Example 5

[0080] A method for preparing a high-temperature-resistant sealing and filling material, comprising the following steps:

[0081] Take 2.0g boron trioxide, 0.1g magnesium oxide, 50g high-alumina powder, 8g silicon dioxide, 0.5g calcium oxide, 1.5g titanium dioxide, 14g chromium trioxide and 0.1g zirconium oxide respectively, mix and stir to obtain mixed refractory powder. After grinding and sieving, 10g sodium fluorosilicate is added to the mixed refractory powder, mixed and stirred, then oscillation ground and sieved through a 270 mesh sieve to obtain a solid material mixture. Take 85g sodium silicate solution to obtain a high-temperature-resistant sealing and filling material. After mixing and stirring, the mixture is uniformly solidified at room temperature for 24 hours to obtain a high-temperature-resistant sealing and filling material.

[0082] The present application uses metal oxides as high-temperature-resistant fillers, and sodium silicate aqueous solution as an adhesive component. The composite filler system ensures that the material has good heat resistance and sealing performance, forms a strong heat-resistant and high-energy silicon-oxygen bond macromolecule, and further solidifies to form a silica network skeleton structure. The sodium silicate aqueous solution hydrolyzes to produce SiO2, and the surface of SiO2 adsorbs hydroxyl groups, which react with Na +The electrostatic effect is formed, the material system structure is stable, the bonding strength is high, the high temperature strength decreases little, the heat resistance, water resistance and acid resistance are good. The high aluminum fine powder is used to improve the compactness of the material, the high aluminum fine powder reacts with silicate to generate silicate in the high temperature process, the bonding film has excellent high temperature resistance. The zirconium oxide, magnesium oxide and calcium oxide are added into the system as good stabilizers and play the role of improving the melting point. The chromium trioxide is used to greatly reduce the viscosity of the adhesive, reduce the content of the adhesive and water, also play the role of preventing cracking, form the low cost, easy preparation, high temperature resistance and strong bonding performance of the high temperature resistant sealing and filling material. Referring to the attached Figure 1 The scanning electron microscope image of the high temperature resistant sealing and filling material prepared according to the case implementation 1 is shown in the figure, and it can be seen from the figure that the prepared high temperature resistant sealing and filling material is in a uniform distribution state.

[0083] The particle size distribution of the high temperature resistant sealing and filling material powder prepared according to the embodiment 1 is more than 90% below 40 μm.

[0084] The high temperature resistant sealing and filling material is finally designed and prepared by adding silica, alumina, zirconia, titanium dioxide, magnesium oxide and the like into the filler to improve the high temperature resistance of the silicate adhesive. Referring to the attached Figure 2 The change photos of the high temperature resistant sealing and filling material prepared according to the case implementation 1 before and after the high temperature of 1200 DEG C. From Figure 2 It can be seen that the high temperature resistant sealing and filling material prepared by the application has excellent high temperature resistance, and after the high temperature of 1200 DEG C, the material does not have the phenomena of bubbling, cracking, burning and pulverization. The thermal weight loss rate of the sample is 0.035%. According to the adhesive shear strength test method, the bonding force performance of the high temperature resistant sealing and filling material prepared according to the case implementation 1 can reach 4.6 Mpa through the tensile shear test.

[0085] Although the application is disclosed as above with preferred embodiments, it is not intended to limit the application, any person skilled in the art can make possible changes and modifications without departing from the spirit and scope of the application, therefore, the protection scope of the application should be limited by the scope defined by the claims of the application.

Claims

1. A high temperature resistant, seal-filling material, characterized by, The high-temperature-resistant filler, the binder and the curing agent, wherein the high-temperature-resistant filler is a metal oxide powder containing high-aluminum fine powder, chromium sesquioxide, boron sesquioxide, magnesium oxide, silicon dioxide, titanium dioxide, calcium oxide and zirconium oxide, the binder contains sodium silicate, and the curing agent contains sodium fluorosilicate.

2. The high temperature resistant, hermetically sealed material of claim 1, wherein, The high-temperature-resistant filler, the curing agent and the binder are prepared according to the following weight parts: 70-90 parts of the high-temperature-resistant filler, 8-12 parts of the curing agent and 85-95 parts of the binder.

3. The high temperature resistant, hermetically sealed material of claim 1, wherein, The mass parts of the substances in the high-temperature-resistant filler satisfy: 48-55 parts of high-aluminum fine powder, 10-15 parts of chromium sesquioxide, 2.0-3.0 parts of boron sesquioxide, 0.1-0.4 parts of magnesium oxide, 8-15 parts of silicon dioxide, 1.5-3.5 parts of titanium dioxide, 0.5-1.0 parts of calcium oxide and 0.1-0.3 parts of zirconium oxide.

4. The high temperature resistant, hermetically sealed material of claim 1, wherein, The high-aluminum fine powder contains ≥70% of aluminum.

5. The high temperature resistant, hermetically sealed material of claim 1, wherein, The sodium silicate satisfies at least one of the following conditions: The sodium silicate contains 8.5% of sodium oxide Na2O and 27.3% of silicon dioxide SiO2; The sodium silicate has a modulus of 2.4 and a pH value of 8-10.

6. The high temperature resistant, hermetically sealed material of claim 1, wherein, The Na2SiF6 content in the curing agent is not less than 99.0%.

7. The high temperature resistant, hermetically sealed material of claim 1, wherein, The particle size of the chromium sesquioxide, the boron sesquioxide, the magnesium oxide, the silicon dioxide, the titanium dioxide, the calcium oxide and the zirconium oxide ranges from 0.1 to 10 μm.

8. A method of producing a high-temperature-resistant, hermetically sealed filling material according to any one of claims 1 to 7, characterized in that The method comprises the following steps: The high-aluminum fine powder, the chromium sesquioxide, the boron sesquioxide, the magnesium oxide, the silicon dioxide, the titanium dioxide, the calcium oxide and the zirconium oxide are ground and sieved to obtain high-temperature-resistant filler mixed particles; The sodium fluorosilicate is ground and dispersed in a mortar and sieved to obtain curing agent particles; The obtained curing agent particles are added to the obtained high-temperature-resistant filler mixed particles, which are ground and sieved to obtain solid material mixture; The sodium silicate solution is added to the obtained solid material mixture, and the mixture is stirred uniformly to obtain the high-temperature-resistant sealing and filling material.

9. The production method according to claim 8, characterized by, The preparation method satisfies at least one of the following conditions: The high-aluminum fine powder is ground and sieved from bauxite, and the sieving mesh number is 320; The sieving mesh number of the solid material mixture is 270; The mass ratio of the binder to the solid material mixture is (45-50):(50-55); The curing condition of the high-temperature-resistant sealing and filling material is room temperature curing, and the curing time is 24 hours.

10. Use of a high temperature resistant, sealable, potting material, characterized in that The high-temperature-resistant sealing and filling material is the high-temperature-resistant sealing and filling material according to any one of claims 1 to 9.